Traditional foods from the Black Sea Area countries: minerals and trace elements content - Costa, H.S. (2012)
Minerals and trace elements and are essential for biological processes and play a vital role in normal growth and development. Low intake or reduced bioavailability of minerals may lead to deficiencies, which causes impairment of body functions. Due to the unquestionable importance of minerals in human nutrition, sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), copper (Cu), phosphorous (P), zinc (Zn), manganese (Mn) and selenium (Se) are being determined in traditional foods from Black Sea Area countries, in the frame of the European Project BaSeFood (Sustainable Exploitation of Bioactive Components from the Black Sea Area Traditional Foods). The aim of this study was to produce new analytical data of minerals and trace elements content in traditional foods in order to highlight their potential positive health effects. All minerals and trace elements were analysed by inductively coupled plasma - optical emission spectrometer (ICP-OES) except for selenium which was performed by graphite atomic absorption spectroscopy in the selected traditional foods from Black Sea Area countries. The methods used in this study are accredited methods by ISO/IEC/17025 or successful participation in proficiency testing schemes. Na and K were the most abundant minerals in the selected traditional foods. For sodium the highest level was found in wild plum sauce from Georgia (561 mg/100 g) and in herbal dish from Romania (618 mg/100 g). The highest content in K (937 mg/100 g), Mg (346 mg/100 g), Cu (1.24 mg/100 g), P (681 mg/100 g) and Zn (5.47 mg/100 g) was found in roasted sunflower seeds from Ukraine. With respect to Mn, herbal dish was the sample with the highest content (2.09 mg/100 g) from those already analysed. Ca and Fe presented the highest level in nettles with walnut sauce from Georgia (452 mg/100 g sample and 5.2 mg/100 g, respectively). The analytical results are given per 100 g of edible portion. A great variability was found for the analysed traditional foods from Black Sea Area countries. The samples with highest mineral content were nettles with walnut sauce, halva, roasted sunflower seeds, wild plum sauce and cottage cheese with dill and garlic.